Solidaritas Sosial Mahasiswa Asal Kabupaten Pegunungan Bintang Dalam Menempuh Studi - Deal, Pison; Yuliana, Yuliana; Idris, Usman (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The purpose of this study is to describe and analyse the form of social solidarity among fellow students living in the Pegunungan Bintang dormitory, and then to describe the efforts made to strengthen social solidarity among them. The research method used is descriptive qualitative with ethnographic approach. The data collection techniques used were in-depth interviews and observation. The research informants were purposively selected. The data analysis techniques include the stages of processing and preparing the data for analysis, reading the whole data, analysing the data in more detail by coding the data, applying the coding to describe the themes for analysis, re-presenting the themes and descriptions in the form of narratives, and interpreting and interpreting the data. The results showed that the form of social solidarity that exists among the students living in the Pegunungan Bintang dormitory is mechanical solidarity. The mechanism built to strengthen social solidarity among fellow students living in the Star Mountains dormitory by implementing mandatory rules for all members of the dormitory residents to help and support each other. In addition, the dormitories also often share meals, sports, religious activities by organising joint worship services, ceremonial celebrations and recreational activities.